Effects of consecutive days of match play on technical performance in tennis - Gescheit, D. T.; Duffield, R.; Skein, M.; Brydon, N.; Cormack, S. J.; Reid, M. (Journal of Sports Sciences, 2017)
Elite tennis is characterised by repeated bouts of up to 5-set match play, yet little is known about the technical requirements of shots played. This study therefore investigated technical performance changes over consecutive days of prolonged, simulated tennis match play. A total of 7 well-trained men tennis players performed 4 consecutive days of competitive 4-h match play. Matches were notated to determine between-day changes in groundstroke and serve performance, as well as point and match durations. Changes =75% likely to exceed the smallest important effect size (0.2) were considered meaningful and represented as effect size ± 90% confidence interval. Effective playing time reduced on days 3 and 4, alongside likely increases in "stretch" groundstrokes over the 4 days (mean effect size ± 90% confidence interval; 0.57 ± 0.38) and "stretch" backhand returns on days 2 and 3 (0.39 ± 0.54 and 0.67 ± 0.55). Relative unforced errors increased on day 4 (vs. day 2; 0.36 ± 0.22) and second-serve winning percentage reduced after day 1 (-0.47 ± 0.50). Further, a likely increase in emotional outbursts characterised day 3 (vs. day 2; 0.73 ± 0.57). Consecutive-day match play impairs hitting accuracy, stroke positioning and emotional responses; an understanding of which prepares players for elite-standard tennis tournament play.